The dynamics of health care for children with cancer in the time of COVID-19 - Silva, Karina de Avellar; Castro, Luciana Souza de; Silva , Laura Johanson da; Souza, Sônia Regina de; Carvalho, Wânia Priscila Melo de; Noronha, Roberta Dantas Breia de (Seven Editora, 2023)
Objectives: To map the scientific production related to the repercussion of COVID-19 on the health of oncological children and to identify the challenges related to this public in the current context of the pandemic. Methodology: this is an integrative review of the literature, consisting of a bibliographic survey and a review of relevant studies published on the CAPES journal portal from January 2020 to October 2021. Six methodological steps were followed and the research strategy with the acronym PICo was used to construct the guiding question. Of the material collected, only 17 works were eligible, according to the objective of the research. Results: In the analyzed works, the main findings were: the relationship between the clinical course of COVID-19 disease in pediatric cancer patients and the challenges related to this public in the current context of the pandemic. Conclusion: This study allows us to conclude that in general, the SARS-COV-2 infection did not have a significant impact on the clinical picture of children and adolescents with cancer, and the treatment presented challenges in times of pandemic. DOI:https://doi.org/10.56238/emerrelcovid19-046